2003
DOI: 10.1213/01.ane.0000061585.09157.66
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Obstructive Sleep Apnea as a Risk Factor for Unanticipated Admissions in Outpatient Surgery

Abstract: In patients scheduled for outpatient surgery in a large academic practice, the diagnosis of obstructive sleep apnea confirmed by polysomnography was not an independent risk factor for unanticipated hospital admission or for other adverse perioperative events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 23 publications
3
52
0
3
Order By: Relevance
“…[25][26][27][28][29][30][31] Only a few studies have evaluated postoperative complications in patients who underwent other types of surgery. 22,[32][33][34][35][36] Our study complements this growing body of literature by demonstrating that OSA patients undergoing different types of surgery have an increased rate of postoperative complications, mainly oxygen desaturation. In a retrospective study of 101 patients with OSA who were undergoing hip replacement or knee replacement, Gupta et al 22 demonstrated that patients with OSA have an increased incidence of total postoperative complications and major complications.…”
Section: Discussionsupporting
confidence: 64%
“…[25][26][27][28][29][30][31] Only a few studies have evaluated postoperative complications in patients who underwent other types of surgery. 22,[32][33][34][35][36] Our study complements this growing body of literature by demonstrating that OSA patients undergoing different types of surgery have an increased rate of postoperative complications, mainly oxygen desaturation. In a retrospective study of 101 patients with OSA who were undergoing hip replacement or knee replacement, Gupta et al 22 demonstrated that patients with OSA have an increased incidence of total postoperative complications and major complications.…”
Section: Discussionsupporting
confidence: 64%
“…Among a cohort of 234 patients with OSA who underwent ambulatory surgery and a similar number of matched control subjects, the odds of adverse events (OR 1.67; 95% CI 0.40 to 6.97) and unplanned admission to hospital (OR 1.36; 95% CI 0.77 to 2.46) did not differ significantly between OSA and control subjects. 12 In a more recent observational cohort study in over 3,500 patients undergoing ambulatory surgery, a questionnaire and propensity modelling were used to identify patients with known and suspected OSA (4.4% and 4.8%, respectively). This study identified positive associations between OSA and the number of intubation attempts, Cormack-Lehane laryngoscopy grade, and probability of vasoactive drug use, 13 but no relationship was found with major cardiorespiratory events or unplanned admission to hospital.…”
Section: Discussionmentioning
confidence: 99%
“…106,107 These studies found that the presence of OSA did not increase the rate of unplanned hospital admissions in patients who underwent outpatient surgical procedures. Stierer et al used a prediction model in a cohort of ambulatory surgical population to assess the probability of sleep apnea.…”
Section: Nocturnal Pulse Oximetrymentioning
confidence: 99%